Exploring Novel Foods: Consumer Willingness and Acceptance of Edible Insects as a Sustainable Alternative Protein Source in Saudi Arabia - Samar Refat Alabdulmohsen; Hala Hazam Al-Otaibi (Foods)
Edible insects are emerging as a sustainable and eco-friendly alternative protein source, addressing global challenges in food security and environmental sustainability. This study investigates the willingness and acceptance of edible insects as sustainable alternative protein sources among Saudi participants, focusing on sociodemographic and attitudinal factors. A cross-sectional survey involving 2208 participants revealed that males and younger individuals (18–34 years) exhibited greater willingness to consume EIs, driven by environmental concerns, health benefits, and positive beliefs. Women and older participants showed higher levels of food neophobia, disgust, and uncertainty. Sociocultural barriers such as fear, a lack of familiarity, and perceptions of edible insects as unclean or forbidden were significant obstacles to acceptance and willingness. Interestingly, the education level did not significantly influence willingness, suggesting that cultural and religious norms may overshadow its impact. These findings underscore the need for targeted campaigns emphasizing the health, environmental, and sustainability benefits of edible insects, alongside culturally sensitive approaches to overcome psychological and social barriers. This research provides valuable insights to guide strategies for integrating EIs into Saudi diets as a step toward enhanced food security and environmental sustainability.